Building and Automating Penetration Testing Labs in the Cloud : Set up cost-effective hacking environments for learning cloud security on AWS, Azure, and GCP /: Set up cost-effective hacking environments for learning cloud security on AWS, Azure, and GCP. (2023) - Lat, Joshua Arvin
No abstract available